Analysis of misaligned journal bearing lubrication performance considering the effect of lubricant couple stress and shear thinning. (25th February 2021) - Zhu, Junchao; Qian, Haiyu; Wen, Huabing; Zheng, Liangyan; Zhu, Hanhua
ABSTRACT: This paper investigates journal bearings, and builds a lubrication model taking into account misalignment, the lubricant couple stress effect and shear thinning. In order to explore the sensitivity of couple stress fluid lubrication performance to oil film thickness, we introduce the critical oil film thickness coefficient. The results show that the sensitivity increases with the increase of the couple stress coefficient, and it is highest in the area of minimum oil film thickness. Compared with a parallel journal, increases in the misalignment angle strengthen the effect of couple stress. Shear thinning also plays an important role in bearing lubrication performance. For a low oil inlet temperature, the effect of shear thinning increases with the increase of the couple stress parameter. For a high oil inlet temperature, the influence is negligible. An increase in the misalignment angle will not further enhance the effect of shear thinning.